Adjustment of prudential norms, determining vector of the banking sector development - N. V. Gryzunova (Управление)
Currently, the Bank of Russia carries out radical reforms in the administration system of banking supervision and regulation. You can observe the interaction between monetary policy and macro prudential policy. The purpose of the traditional regulator is protection of investors', shareholders', customers' capital. The main problem of the Russian economy is the shortage of investment and working capital from non-credit institutions and the difficulty to get a foothold lending. The main objective of the banking system reform is to create additional sources of investment for non-credit institutions. The tightening Supervisory requirements although eliminate the total bank risks, but reduce business activity and agility of the banking system. The curve of investment demand in the Russian economy is flat, that characterizes the low profitability of investments and the weak dependence on interest-rate policy. In this connection, it has been suggested to consider investment companies as the main criterion of competitiveness and the main argument in decision-making about granting a credit line.The feasibility of the allocation of investment criteria in the monetary rule has been shown in the article. The urgency proportional distribution of regulatory indicators of banking supervision by tier banking system, which are formed from the pacing of functional and regional specificity, – has been substantiated. The mechanism of price stability based on the clustering of financial institutions has been offered. It has been suggested to use the investment criteria as justification for a transfer service of non-bank organization to another bank cluster. Possible trends and implications of key planned reforms of the banking system including the bank's tier and the distribution tier of powers and functions have been analysed.Due to measures of preventive supervision and bank clustering, it is possible to expect regional market segmentation, improving the effectiveness of internal control systems, based on the distribution of the control functions in bank tiers, simplify management and risk reduction in accordance with the profile of the company and the level of the bank's operations. It has been proved in the paper that a focused segmentation of the credit market allows us to reduce the credit risks for banks, as well as to link market characteristics with the business models of each cluster.